Effect of Cu on microstructure, mechanical properties, corrosion resistance and cytotoxicity of CoCrW alloy fabricated by selective laser melting. (May 2018) - Lu, Yanjin; Ren, Ling; Xu, Xiongcheng; Yang, Yang; Wu, Songquan; Luo, Jiasi; Yang, Mingyu; Liu, Lingling; Zhuang, Danhong; Yang, Ke; Lin, Jinxin
Abstract: In the study, CoCrWCu alloys with differing Cu content (2, 3, 4 wt%) were prepared by selective laser melting using mixture powders consisting of CoCrW and Cu, aiming at investigating the effect of Cu on the microstructures, mechanical properties, corrosion behavior and cytotoxicity. The SEM observations indicated that the Cu content up to 3 wt% caused the Si-rich precipitates to segregate along grain boundaries and in the grains, and EBSD analysis suggested that the Cu addition decreased the recrystallization degree and increased the grain diameter and fraction of big grains. The tensile tests found that the increasing Cu content led to a decrease of mechanical properties compared with Cu-free CoCrW alloy. The electrochemical tests revealed that the addition of Cu shifted the corrosion potential toward nobler positive, but increased the corrosion current density. Also, a more protective passive film was formed when 2 wt% Cu content was added, but the higher Cu content up to 3 wt% was detrimental to the corrosion resistance. It was noted that there was no cytotoxicity for Cu-bearing CoCrW alloys to MG-63 cell and the cells could spread well on the surfaces of studied alloys. Meanwhile, the Cu-bearing CoCrW alloy exhibited an excellent antibacterial performance against E.coli when Cu content was up to 3 wt%. It is suggested that the feasible fabrication of Cu-bearing CoCrW alloy by SLM using mixed CoCrW and Cu powders is a promising candidate for use in antibacterial oral repair products. This current study also can aid in the further design of antibacterial Cu-containing CoCrW alloying powders. Graphical abstract: fx1